Fasting in Hinduism, Buddhism and Islam: A Comparative Study - Md. Thowhidul Islam (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Voluntary abstinence from food has been a spiritual purification rite in many religions. Penitence, purification and sacrifice are the major aims. Fasting in Hinduism is the denial of the physical needs of the body for the sake of spiritual gains. Hindus observe a period of fasting during the month of ‘Shravan’ (July/August), a holy month with religious festivals such as ‘Janmastami’ (Lord Krishna’s birthday) and ‘Rakhibandhan’ (when sisters tie a ‘rakhi’ on their brothers). Many Hindus also fast all year round on certain days of week for example, on Monday for Lord Shiva and his wife Goddess Durga. According to Hindu scriptures, fasting helps to create an attunement with the Absolute by establishing a harmonious relationship between the body and the soul. The Buddhist tradition prefers to abstain from eating meat, since this involves the killing of living beings. According to the Buddhist monastic rules, the Vinaya, monks and nuns should have only two meals a day, in the early morning and before noon, and abstain from food for the rest of the day. On festive days, especially at full and new moon, laypeople also follow those rules. There is also some occasional fasting such as the fasting for Lokesvara, which is supposed to cause the birth of a son; fasting for Tara, which frees one from illness and dangers. The Tibetan Buddhist practice of Nyungne (abiding in the fast) has been gaining increased attention. It is two and a half-day practice, which involves the keeping of strict vows, silence and fasting. Fasting the lunar month of Ramadan is one of the five fundamentals of Islam. It has been an obligatory duty ordained by the Almighty Allah for all the adult observant Muslims except who are ill, traveling or pregnant. There are also some other voluntary fasting in Islam. Fasting, in Arabic called Sawm, is abstinence from eating, drinking or sexual activity from sunset to sundown during the month of Ramadan. In Islam, fasting is an important act of worship done for Allah, whereby a Muslim draws closer to his Lord. Because of fasting, the sincerity of faith and devotion to Allah should become all the more evident. The purpose of fasting is to develop God-consciousness (Taqwa), which can lead to the forth of goodness and virtue in life and hereafter. The learning of self-restrains from fasting is capable enough to lead a purer life in this world as well as to an eternal life of happiness in the next. After having a comprehensive study and finding out the similarities and dissimilarities among the fasting tradition of Hinduism, Buddhism and Islam, this paper is mainly aimed at proving the highness and glory of fasting system of Islam in gaining its material and spiritual objectives.